Influence of prenatal aquatic activities on fetal outcomes and maternal physical and mental outcomes: a systematic review and meta-analysis - Kun Zhao; Junmiao Xu; Jingting Zhao; Rongrong Chen; Yuhan Wang; Xiangming Ye; Feifei Zhou (BMC, 2024)
Abstract Background Aquatic activities are becoming increasingly popular as a form of exercise during pregnancy. However, the effects of these activities on the physical and mental health outcomes of pregnant women during and after pregnancy as well as fetal outcomes remain unclear. This meta-analysis evaluated the current evidence regarding the effects of aquatic activities during pregnancy on neonatal and maternal outcomes. Methods Three databases (PubMed, Cochrane Central electronic database, Embase) were searched from inception to July 17, 2024 for randomized controlled trials (RCTs) comparing the effects of aquatic activities versus standard prenatal care or no exercise on neonatal and maternal outcomes. Pooled outcome measures were determined using random-effects models. Results Ten RCTs including 1949 patients met the criteria for inclusion in this meta-analysis. The results showed that prenatal aquatic activities could significantly improve maternal weight control (mean difference [MD]= -0.91, 95% confidence interval [CI]= -1.64 to -0.18, P = 0.01, I2 = 0.00%), improve maternal quality of life (standard mean difference [SMD] = 0.16, 95%CI = 0.03 to 0.28, P = 0.01, I2 = 0.00%), and extend fetal birth length (MD = 0.48, 95%CI = 0.10 to 0.87, P = 0.01, I2 = 0.00%) compared with standard prenatal care or no exercise, while no significant differences were observed in fetal birth weight, Apgar score at 1 min, Apgar score at 5 min, pH of umbilical cord blood, gestational age, rate of preterm delivery, incidence of postnatal depression and mode of delivery. Conclusions Prenatal aquatic activities can significantly improve maternal weight control and quality of life during pregnancy, and may promote longer birth length. However, additional studies are needed to confirm these findings.